Analysis of Directive Speech Acts in the Film "Imperfect: Karier, Cinta & Timbangan" - Astuti, Harsi; Wirawati, Denik (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The research is motivated by the importance of knowing the actions or utterance that the speaker wishes to convey to the interlocutor. So that the interlocutor can catch the intent conveyed by the speaker. Based on this, this study aims to: (1) describe the form o directive speech acts in the film "Imperfect: Karier, Cinta & Timbangan". (2) describe the function of directive speech acts in the film "Imperfect: Karier, Cinta & Timbangan". This type of research is descriptive qualitative. The data collection method used is listening method with basic tapping techniques, advanced listening techniques free of involvement, and note-taking techniques. The data analysis method used is the pragmatic equivalent method with determining elements, and advanced comparative comparison techniques equate. The results of this study are that there are 154 data classified as follows, there are 36 data in the form of orders, 30 data in the form of requests, 17 solicitation form data, 18 data in the form of advice, 35 data in the form of criticism, and 18 data in the form of prohibilitions.